Systemic inflammatory response syndrome and multiple organ dysfunction syndrome caused by acute mountain sickness: a case report and literature review - Wang, Bowen; Peng, Mengjia; Kou, Guoyong; Fang, Fei; Gao, Jinhang (Frontiers in Physiology, 2025)
Acute mountain sickness (AMS) is a common condition following rapid exposure to high altitude, though severe complications such as acute gastrointestinal bleeding, systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome (MODS) are rare. Herein, we report a case of SIRS and MODS in a young traveler who visited Lhasa, Tibet (elevation 3,650 m). Three days after arrival, the patient developed headache, abdominal pain, significant hematemesis, and persistent hypotension. Gastroscopy revealed diffuse bleeding of the gastric mucosa. Laboratory tests indicated multi-organ dysfunction involving the lungs, liver, and kidneys. The patient responded well to conservative treatment of continuous oxygen supplementation. This case represents one of the first reported instances of acute gastric mucosal injury and MODS induced by AMS, underscoring the significant medical risks associated with high-altitude environments.